Purchase intention towards remanufactured smartphone : a study on young consumer [electronic resource] - Joan Ann Johnny Saling 1991- 638656; Thoo Ai Chin 1990- supervisor 636464; Fakulti Pengurusan 538641 (2016)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2016